Carring behavior, discipline, and competence as predictors of service quality in the RSU Ogan Ilir - Jauhari Jauhari; Tien Yustini (Institute of Computer Science (IOCS), 2026)
This study aims to analyze and empirically verify the influence of caring behavior, discipline, and competence on the service quality of employees at the Ogan Ilir Regional General Hospital, both partially and simultaneously. The research employed a quantitative method with survey, confirmatory, and verificative approaches. This study is categorized as associative research, focusing on the relationships among variables. The research population consisted of 118 employees, all of whom were included as research samples using a saturated sampling technique. The types of data comprised primary and secondary data, collected through observation, questionnaire-based interviews, and documentation. The data analysis technique used was multiple linear regression with SPSS version 30. The findings indicate that caring behavior, discipline, and competence have a positive and significant effect on improving service quality, both partially and simultaneously. These three variables demonstrate a substantial (strong) relationship of 81.6% with the improvement of service quality. This research contributes to developing comprehensive human resource management science and further research in this field. Improving service quality can be done by simultaneously paying attention to aspects of caring behavior, discipline, and competence